Fórum do Futuro : Vita Nova : 2021. - Basar, Shumon; Blanc, Guilherme; Ramos, Filipa; Sutela, Jenna (Berlin : Bom Dia Boa Tarde Boa Noite, 2021)
Treister, Suzanne ; K Allado-McDowell ; GPT-3 ; Zhou, Feifei ; Basco, Tosh ; Ferreira da Silva, Denise ; Jonas, Joan ; Basire, James
boek